Correlations of Human Epithelial Growth Factor Receptor 2 Overexpression with MUC2, MUC5AC, MUC6, p53, and Clinicopathological Characteristics in Gastric Cancer Patients with Curative Resection - Kwang Kuk Park; Song I Yang; Kyung Won Seo; Ki Young Yoon; Sang Ho Lee; Hee Kyung Jang; Yeon Myeong Shin (Gastroenterology Research and Practice)
Background. The purpose of this study was to evaluate the relationships between HER2 overexpression in the tumor and MUC2, MUC5AC, MUC6, and p53 status and clinicopathological characteristics of gastric cancer patients. Methods. This retrospective study included 282 consecutive patients with gastric cancer who underwent surgery at the Kosin University Gospel Hospital between April 2011 and December 2012. All tumor samples were examined for HER2 expression by immunohistochemistry (IHC) and MUC2, MUC5AC, MUC6, and p53 expression by staining. A retrospective review of the medical records was conducted to determine the correlation between the presence of HER2 overexpression and clinicopathological factors. Results. The HER2-positive rate was 18.1%. Although no association was found between HER2 expression and MUC5AC, the expression of MUC2, MUC6, and p53 was significantly correlated with HER2 positivity, respectively (P = 0.004, 0.037, 0.002). Multivariate analysis revealed that HER2 overexpression and nodal status were independent prognostic factors. Conclusions. HER2 overexpression in gastric carcinoma is an independent poor prognostic factor.